Police arrest five in weekend drug raids: Final Edition (Edmonton journal, 1993)
Long Ngot Pham, 31, Chinh Thi Vu, 27, Mai Thi Le, 29, and Thao Thi Doan, 27, are all charged with possession of a narcotic for the purpose of trafficking.